Strategi Pondok Pesantren dalam Mengembangkan Sumber Daya Manusia (SDM) Santri di Bidang Kewirausahaan (Studi Kasus Pondok Pesantren Raudhatul Ulum 1 Meranti) - Sa’adi, Sa’adi; Firayanti, Yuni; Marhamah, Marhamah (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
This study aims to describe and analyze the strategies employed by Pondok Pesantren Raudhatul Ulum 1 Meranti in developing the human resources (HR) of its students (santri) in the field of entrepreneurship. The background of this research highlights the importance of empowering santri not only with spiritual and academic competencies but also with economic skills to support their independence in the future. This research uses a descriptive qualitative method, with data collected through observation, in-depth interviews with the pesantren leadership, entrepreneurship program administrators, santri, and documentation. The data analysis process includes data reduction, data presentation, and drawing conclusions. To strengthen the analysis, a SWOT approach is also utilized. The findings indicate that the HR development strategy for santri is implemented through several key steps: general and specific entrepreneurship training, mentoring by experienced individuals, hands-on practice through pesantren business units, collaboration with external parties such as BSI Maslahat and alumni, as well as the utilization of digital technology for product marketing. This strategy has a positive impact on enhancing technical skills, fostering entrepreneurial character, building independence, and preparing students for the business world. Evaluation is conducted periodically through observation, activity reports, and interviews with current and former santri. The study concludes that the strategy implemented by Pondok Pesantren Raudhatul Ulum 1 Meranti is holistic, practice-oriented, based on Islamic values, and effective in creating high-quality, economically self-reliant santri.